3(8x-2)+6x/3=72

Simple and best practice solution for 3(8x-2)+6x/3=72 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(8x-2)+6x/3=72 equation:



3(8x-2)+6x/3=72
We move all terms to the left:
3(8x-2)+6x/3-(72)=0
We multiply parentheses
24x+6x/3-6-72=0
We multiply all the terms by the denominator
24x*3+6x-6*3-72*3=0
We add all the numbers together, and all the variables
6x+24x*3-234=0
Wy multiply elements
6x+72x-234=0
We add all the numbers together, and all the variables
78x-234=0
We move all terms containing x to the left, all other terms to the right
78x=234
x=234/78
x=3

See similar equations:

| 8=3(3x+8)x | | 51-x=5x-15=3x+7 | | (15x-2)(5x+3)=5 | | 11u=3u+16 | | 3x-8+2x+28=55 | | 3(v-8)-8v=-29 | | F(x)=3x^2+6x−5 | | 3Xn=2X9 | | 20x+10x=11 | | 3/4*f=15 | | x/2-2/3=3x+4/2 | | 16-2t=t=9+4t | | 60=6x+4x | | 2(3x+5)+6=-44 | | 5a−4a=12 | | u/8+15=25 | | 5x+3=x-25 | | 4x8=28 | | 4y-6-3y=-5 | | 5(3z-1)-3(z+8)=5(z+1) | | 9x+63=20 | | -6(t-2)-(t+2)=7 | | 2x-(9x+9)=9x-41 | | 100^100÷50^50=200x | | 8x+3=11x-18 | | PT=7x=3 | | -2/5=1/3m+35 | | 2x-(4x+9)=2x-41 | | (4*x-2)/3=(2*x)/7 | | 5x/7+3=27 | | 5/12=1x/36 | | u^2-3u-3=0 |

Equations solver categories